Implementasi Kebijakan Pemerintah Kabupaten Pasuruan dalam Menangani Kasus Perkawinan Anak Melalui Peraturan Bupati Nomor 12 Tahun 2019 - Ananda Sri Wilujeng; Agus Zainal Abidin; Retno Wulan Sekarsari (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
A major social issue in Pasuruan Regency, particularly in Tutur District, is child marriage. Even after the issuance of Pasuruan Regent Regulation No. 12 of 2019 concerning the Development of Child-Friendly Districts, the number of child marriages remains a problem that needs to be addressed. The purpose of this study is to examine how Regent Regulation No. 12 of 2019 of the Pasuruan Regency Government prohibiting child marriage is implemented in Tutur District and to identify both supporting and inhibiting factors. Based on the theory of George C. Edward III, this study uses a descriptive qualitative approach, focusing on aspects of communication, resources, disposition, and bureaucratic structure. Data were collected through semi-structured interviews, observation, and documentation of purposefully selected informants. The interactive model of Miles, Huberman, and Saldana was then used for analysis. The results show how successfully the policy has been implemented. Cross-sector collaboration and various outreach activities have been used to implement the communication component. In terms of resources, implementers have sufficient strength and knowledge, but they are still limited by financial constraints and the scope of the extension program. Although not yet fully defined, the bureaucratic structure is supported by clear processes, and the disposition of implementers demonstrates a high level of commitment. Cross-sector collaboration, long-term prevention initiatives, and the participation of religious and community leaders are essential supporting elements. A tolerant society toward child marriage, low public awareness and education, and limited program funding are barriers. Therefore, to maximize child marriage prevention, collaboration must be strengthened, implementer capacity must be increased, and a community-based approach must be employed.